Meta AI dan Literasi Bahasa Arab Digital: Tantangan dan Peluang Pembelajaran Mahasiswa di Perguruan Tinggi Islam - Ani Susilawati; Nurfauziah Fatawi; Fikri Muhammad Hanif (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
The development of artificial intelligence (AI) presents new opportunities to improve digital literacy. In line with that, the government has ratified Circular Letter No. 9 of 2023 concerning World Ethics, which is currently entering the digital world 5.0, which is a continuation of the era of the industrial revolution 4.0. In addition, the vision of AI aims to be used as a solution to the problems of modern society, including those in Higher Education. This study reveals the challenges and opportunities of using Meta AI, especially through integration with the WhatsApp platform, to strengthen students' digital Arabic literacy in Metro cities. This study uses a qualitative approach, including in-depth interviews, observation, and documentation.  The object of this research is students of the Arabic Language Education (PBA) study program and the Arabic Language and Literature Study program (BSA) of Jurai Siwo State Islamic University, Lampung, and Ma'arif University, Lampung. The results of this study show that Meta AI offers opportunities through adaptive learning, increased accessibility, and support for self-paced learning. However, several challenges were also identified, such as limited student technical understanding, issues of academic ethics, language accuracy, platform integration, and privacy and regulatory concerns. The findings of this study emphasize the need for comprehensive pedagogical strategies and institutional policies to ensure the effective and ethical use of Meta AI to strengthen digital Arabic literacy.